Students’ Digital Literacy Skill To Solve Learning Problems - Muh. Idris P; Sukardi Weda; Andi Hamzah Fansury (Postgraduate Bosowa University, 2023)
The purpose of this study was to analyze whether these digital skills are able to solve students' problems. Perceptions of students about digital literacy XI OTKP SMK Darussalam Makassar. This research is a qualitative research. data collection technique by using a interview and giving a questionnaire. The researcher took 19 students of class XI OTKP SMK Darussalam Makassar as research subjects. the researcher use questionnaire for 19 students to know about the survey in the impact digital literacy for resolve learning problems. The interview for the 7 students, to know about the students’ perception about the Digital literacy in learning process. the student statements above, concluded that digital literacy in education has a positive impact on students, easy access to various kinds of information needed to solve problems, becomes a new habit for students, namely seeking information not only from textbooks or from teachers. Students also become more critical and communicate a lot with their friends about the information they get. Based on the results of the interviews that have been conducted, students answered that the teacher is the main aspect that must provide a comfortable situation in the classroom. This proves that the role of parents and teachers is very important at this stage and Students’ statements also express positive things about digital literacy in their learning process